Potential Application of Pyroptosis in Kidney Renal Clear Cell Carcinoma Immunotherapy and Targeted Therapy - Qi, Xiaochen; Che, Xiangyu; Li, Quanlin; Wang, Qifei; Wu, Guangzhen (Frontiers in Pharmacology, 2022)
Renal cell carcinoma is a kind of cancer with increasing morbidity and mortality, which is a serious threat to human health. The treatment of renal cell carcinoma, especially KIRC, has always been the focus of clinical treatment. Starting from the TCGA database, this study explored the feasibility of the pyroptosis mechanism applied to KIRC treatment by looking for cancer markers associated with pyroptosis and cancer treatment signature. The obtained samples were clustered by unsupervised clustering analysis to obtain different KIRC subtypes with different pyroptosis expressions. Based on this, gene expression analysis was performed to explore the carcinogenic mechanism that is significantly related to pyroptosis. By using the GDSC database and the ssGSEA algorithm to analyze the different treatment methods of the current popular KIRC, to determine whether pyroptosis plays a role in it. Finally, LASSO regression was used to screen related genes and construct a model to predict the prognosis of patients. Through the above analysis, we proved the feasibility of pyroptosis in the clinical treatment of KIRC, and provided different ideas and suggestions for the clinical treatment of KIRC.